2011
DOI: 10.1128/iai.01162-10
|View full text |Cite
|
Sign up to set email alerts
|

The Neisseria gonorrhoeae Biofilm Matrix Contains DNA, and an Endogenous Nuclease Controls Its Incorporation

Abstract: Neisseria gonorrhoeae has been shown to produce biofilms both in experimental flow chambers and in the human host. Our laboratory has shown that extracellular DNA is an essential component of the gonococcal matrix. We have also identified a gene in N. gonorrhoeae, which we designated nuc. This gene has homology with the staphylococcus-secreted thermonuclease. Our laboratory has characterized nuc through phenotypic analysis of a nuc deletion mutant. Biofilms grown with this strain are significantly thicker and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 23 publications
3
76
0
Order By: Relevance
“…Neisseria gonorrhoeae encodes a thermonuclease homolog (Nuc) that degrades singleand double-stranded DNA and helps remodel N. gonorrhoeae biofilms [17]. Here, we show that N. gonorrhoeae induces NET formation from human neutrophils; however, Nuc degrades the DNA backbone of NETs over time.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…Neisseria gonorrhoeae encodes a thermonuclease homolog (Nuc) that degrades singleand double-stranded DNA and helps remodel N. gonorrhoeae biofilms [17]. Here, we show that N. gonorrhoeae induces NET formation from human neutrophils; however, Nuc degrades the DNA backbone of NETs over time.…”
mentioning
confidence: 81%
“…Parent, Δnuc, and nuc-complement N. gonorrhoeae grew similarly in liquid medium (Supplementary Figure 1A). Piliated, Opa-expressing N. gonorrhoeae of strain 1291 and an isogenic Δnuc mutant were also used [17]; immunoblotting revealed that the strains had identical Opa expression profiles (data not shown).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
See 3 more Smart Citations